Seismic Analysis by Macroelements of Fujian Hakka Tulous, Chinese Circular Earth Constructions Listed in the UNESCO World Heritage List. Issue 10 (25th November 2020) - Briseghella, B.; Colasanti, V.; Fenu, L.; Nuti, C.; Spacone, E.; Varum, H.
ABSTRACT: The overall seismic response of Hakka Tulous, massive traditional earth constructions located in the Fujian Province (China) and part of the UNESCO list of World Heritage buildings, is investigated. For this aim, non-linear static analysis (pushover) was used. Since Tulous are complex circular earth structures (about 50 m in diameter) stiffened by wooden frames along the whole inner perimeter of the circular earth wall, non-linear finite element models are hard to implement because convergence is difficult to achieve and very long computation time would be required given the large number of elements and degrees of freedom. For the above reasons, the equivalent frame approach is often used for masonry structures. Even if a few approximations are needed, non-linear static analysis of even very complex masonry structures can be successfully performed with fewer convergence problems and lower computational efforts. The seismic analysis of a representative circular Tulou is carried out. An extension to circular masonry structures of the analysis by macroelements through the equivalent frame method is hence studied. The results provides insight on the Tulou's failure modes and on its overall seismic response. Since this is the first study on the overall seismic response of these complex earth constructions, further research is needed to deepen our knowledge of their structural behaviour.